PENGARUH REKRUTMEN, DISIPLIN KERJA DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN PADA PT. PLN (Persero) ULP MEDAN SUNGGAL - Ndruru, Tomas Edin S.; Tarigan, Miska Irani; Purba, Saut; Ritonga, Sinar (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2024)
The objective of this investigation is to eval_uate the impact of recruitment, work discipline, and non-physical work environment on the performance of employees at the Medan Sunggal Customer Service Unit of PT PLN (Persero). Quantitative analysis is the methodology employed in this investigation. The data was collected through a questionnaire distribution survey that was administered to 63 (sixty-three) personnel of the Medan Sunggal Customer Service Unit of PT PLN (Persero). The Statistical Package for the Social Sciences (SPSS) software is utilized to conduct multiple linear regression data analysis, while saturated sampling or census sampling techniques are employed for sampling. The data processing conducted yields a multiple linear equation, the results indicating that recruitment has a substantial impact on employee performance. The performance of employees is significantly influenced by their work discipline. The non-physical work environment has a substantial impact on employee performance. The extent of the influence of recruitment, work discipline, and non-physical work environment on employee performance is indicated by the coefficient of determination (R2) of 91.7%. The remaining 8.3% is influenced by factors that are not included in this study. The F test results that H0 is rejected and H1 is accepted. This implies that the recruitment variables, work discipline, and non-physical work environment have a positive and significant impact on employee performance at the Medan Sunggal Customer Service Unit of PT. PLN (Persero).